THE ROLE OF ICE SKATING AND ICE HOCKEY EDUCATION IN EVERY DAY PHYSICAL EDUCATION - MÁRTON, Laura; TAKÁCS, Alexandra; BÉRES, Sándor; GÉCZI, Gábor; BENCZENLEITNER, Ottó (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2016)
Sport and physical education are strategically very important areas for the leaders of the country, which caused serious changes in the education during the last few years. In this study those difficulties were investigated which schools had to face because of the Public Education Act (accepted in 2011), and how the problems were solved, what kind of changes had to be done during the everyday work. The aim of this study was to assess the different opinions about the introduction of everyday physical education (PE) and to investigate why schools chose ice skating and ice hockey to replace the PE lessons. The results show that everyone considers PE lessons useful and that ice skating and ice hockey are popular activities among the participating schools.